Female sex work interventions and changes in HIV and syphilis infection risks from 2003 to 2008 in India: a repeated cross-sectional study. Issue 6 (16th June 2013) - Arora, Paul; Nagelkerke, Nico J D; Moineddin, Rahim; Bhattacharya, Madhulekha; Jha, Prabhat
Abstract : Objectives: We examined if increased spending and coverage of female sex worker (FSW) interventions were associated with declines in HIV or syphilis risk among young pregnant women (as a proxy for new infections in the general population) in the high-burden southern states of India. Design: Repeated cross-sectional analysis. Setting: We used logistic regression to relate district-level spending, number of sexually transmitted infections (STIs) treated, FSWs reached or condoms distributed to the declines in the annual risk of HIV and syphilis from 2003 to 2008 among prenatal clinic attendees in the four high-HIV burden states of Andhra Pradesh, Karnataka, Maharashtra and Tamil Nadu. Participants: 386 961 pregnant women aged 15–24 years (as a proxy for incident infections in the adult population). Interventions: We examined National AIDS Control Organisation (NACO) data on 868 FSW intervention projects implemented between 1995 and 2008. Primary and secondary outcome measures: HIV or syphilis infection. Results: HIV and syphilis prevalence declined substantially among young pregnant women. Each additional STI treated (per 1000 people) reduced the annual risk of HIV infection by −1.7% (95% CI −3.3 to −0.1) and reduced the annual risk of syphilis infection by −10.9% (95%CI −15.9 to −5.8). Spending, FSWs reached or condoms distributed did not reduce HIV risk, but each was significantly associated with reduced annual risk of syphilis infection. There were no major differences between the NACO-funded and Avahan-funded districts in the annual risk of either STI. Conclusions: Targeted FSW interventions are associated with reductions in syphilis risk and STI treatment is associated with reduced HIV risk. Both more and less costly FSW interventions have comparable effectiveness.